Analisis Makna Semiotika Pada Lirik Lagu Di Ujung Hari Karya Ungu - Masagus Muhammad Okta Fakri; Indrawati Indrawati; Hartika Utami Fitri (ScidacPlus, 2023)
A song is a literary work, almost the same as poetry, but sung. The lyrics of the song Di Ujung Hari are a religious song which contains a message, namely conveying how difficult it is to live during a pandemic, when the earth is being hit by serious problems and humans can help each other, and whatever trials they face are only a test from God Almighty so that their creatures will be better. strong. In conducting this research, library research researchers used descriptive qualitative research methods. Qualitative research methods are often also called naturalistic research methods because the research is carried out in a natural setting. Qualitative research is carried out on natural objects that develop as they are, are not manipulated by scientists, and the presence of scientists does not actually influence the dynamics of these objects. The song being studied is the lyrics of a song entitled